An army at dawn : the war in North Africa, 1942-1943 - Atkinson, Rick. (New York : Henry Holt & Co., 2002)
In the first volume of his monumental trilogy about the liberation of Europe in WW II, Pulitzer Prize winner Rick Atkinson tells the riveting story of the war in North Africa. The liberation of Europe and the destruction of the Third Reich is a story of courage and enduring triumph, of calamity and miscalculation. That first year of the Allied war was a pivotal point in American history, the moment when the United States began to act like a great power. Beginning with the daring amphibious invasion in November 1942, An Army at Dawn follows the American and British armies as they fight the French in Morocco and Algeria, and then take on the Germans and Italians in Tunisia. Battle by battle, an inexperienced and sometimes poorly led army gradually becomes a superb fighting force. Central to the tale are the extraordinary but fallible commanders who come to dominate the battlefield: Eisenhower, Patton, Bradley, Montgomery, and Rommel. Brilliantly researched, rich with new material and vivid insights, Atkinson's narrative provides the definitive history of the war in North Africa.
Passage -- Landing -- Beachhead -- Pushing East -- Primus in Carthago -- A country of defiles -- Casablanca -- A bits and pieces war -- Kasserine -- The world we knew is a long time dead -- Over the top -- The inner keep -- Epilogue.
Includes Index
Keywords: World War -- Campaigns -- Africa, North. -- 1939-1945; Operation Torch, -- 1942.; World War -- Campaigns -- Africa, North. -- 1939-1945; Operation Torch; Weltkrieg -- (1939-1945); Geschichte; Operation Torch; Africa, North -- History, Military; Nordafrika